Burnout Dan Kepuasan Kerja Karyawan - Pranitasari, Diah; Lilik Lidyawati; Dodi Prastuti; Pristina Hermastuti; Nung Siti Saodah (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2023)
This research aims to determine the internal and external factors of burnout using self-efficacy and locus of control as internal factors, and work environment and leadership effectiveness as external factors. The influence of these internal and external burnout factors on employee job satisfaction is examined. The study was conducted on employees of CV. Dermaga Mulia Abadi. This is a quantitative study using a survey method. The population of this study is all employees, amounting to 98 employees, and the sampling method used is the saturated sample method, where the sample size is equal to the population size. Data processing used SEM-PLS with smartPLS software. The results of this study conclude that self-efficacy has an influence on job satisfaction by 24.7%. This means that with high self-efficacy, employees are likely to experience high job satisfaction. Locus of control does not affect job satisfaction. The work environment has an influence of 23.9% on job satisfaction. This implies that a comfortable work environment increases employee job satisfaction. Leadership effectiveness has an influence on job satisfaction by 31.5%. This means that effective leadership, involving program planning, organizing, guiding, and assigning tasks well to employees, can significantly increase employee job satisfaction. Leadership effectiveness has the most significant impact on employee job satisfaction